Microbiological monitoring in two areas with different levels of conservation in the mangroves of an Ecological Station, Vitoria, ES (Acta Scientiarum. Biological Sciences, 2016)
Mangroves are classified as permanent preservation areas and regarded as natural nurseries. However, they have suffered several anthropogenic stresses, resulting in their decline. In the light of that, comes the importance of researching their environmental characteristics and revealing possible factors that have led to the degradation of this important ecosystem. The aim of this study was to evaluate the environmental quality of different areas in the mangroves of Ilha do Lameirão Ecological Station through microbiological analyzes of sediment and interstitial water along ten (10) sites, distributed in two areas with different conservation levels (Canal dos Escravos (CE) and Maria Ortiz (MO)) between 2010 and 2012. The microbiological analyzes revealed that MO region, in all seasons of the year, achieved total coliform and thermo-tolerant coliform values above those permitted by the CONAMA Resolution 357/05, fitting the Class 2 conservation standard. The presence of high levels of total and thermo-tolerant coliforms in MO is a strong indicator of impacts originated from the human population and, consequently, the decline of the mangrove itself and the health of human communities surrounding that area.